PTU-014 Impact of Primary Care Education on the Two Week wait Referral Process for GI Cancers. (4th June 2013) - Biswas, S; Willington, A; Ellis, A
Abstract : Introduction: The two week wait referral process was introduced in 2000 to improve cancer prognosis in the UK with an anticipated 20% reduction in cancer-related deaths. The cancer yield has in fact been reported as 9–16%. Referrals should be made on the basis of NICE guidance. Previous studies have highlighted that as few as 53% of referrals from Primary Care have been within NICE guidance. The Government's nine-week "Be clear on cancer" campaign launched in January 2012 via online, TV and radio adverts to increase public awareness of bowel cancer symptoms impacted our service. The proportion of colonoscopies done for the two-week wait service increased from 27% to 48% in the month after the campaign. It is clearly important that referrals made are appropriate to justify this service requirement. This study compares referrals and outcomes before and after a GP education session. Methods: Two week wait GI Referrals to the Horton General Hospital between December 2011 and February 2012 were assessed. A presentation was given to Primary Care Practitioners in May highlighting NICE guidance and referrals were re-audited in June 2012. Results: 100% of referrals met the two week wait target (to clinic, CT scan or endoscopy) and the mean time to first test was 9 days. The results are summarised below. 24% of Upper GI referrals did not meet NICE guidance, mostly patients referred with anaemia above the referral threshold or for dyspepsia without concerning features. The cancer pick-up was 8.6% (2 oesophageal, 2 gastric and 4 pancreatico-biliary). 26% of Lower GI referrals were non-compliant with guidance (mostly due to rectal bleeding or change in bowel habit shorter than the required time). Cancer pick-up was 5.1%. All but one GI cancer was detected in appropriately referred patients. In June 2012 compliance improved to 81% of upper GI and 79% of lower GI referrals. Reasons for referral outside NICE guidance were similar to the previous cohort. Cancer detection rose to 12.9% for Upper GI and 8.6% for Lower GI cancers. All cancers in the second audit were in appropriately referred patients. Conclusion: The study highlights the importance of communication with Primary Care Practitioners who are responsible for referrals for GI cancer exclusion. There have been previous education sessions but despite this there remains an advantage in re-stating the message and keeping regular contact. The cancer detection rate improved with better compliance with NICE guidance and may indicate the value of adhering to this guidance. Larger studies are required to validate this. Disclosure of Interest: None Declared